DEVELOPMENT OF AN ECONOMIC-MATHEMATICAL MODEL FOR PROJECT TEAM FORMATION IN MODERN CONDITIONS: KNOWLEDGE ASPECT - CHAIKOVSKA, INNA; CHAIKOVSKYI, MAKSYM (Herald of Khmelnytskyi National University. Economic sciences, 2021)
An economic-mathematical model of forming the optimal composition of the project team according to the level of knowledge in modern conditions has been developed, which allows to successfully implement the project. The objective function is to maximize the integrated indicator for the selected combination of employees of one division of the enterprise, which will be part of the project team. This integrated indicator is the average value of the appropriate level of knowledge of employees in each required area of knowledge, taking into account the relevant weighting factor. This takes into account the restriction that a potential team member's level of knowledge in the established areas of knowledge should not be lower than the minimum level set by experts. As well as the average value of a group of employees from one unit in each area of knowledge should not be lower than the average level set by experts. If there are no employees with the appropriate level of knowledge in the divisions of the enterprise, a combination of employees with a minimum deviation is selected. The model involves the use of elements of combinatorics to determine possible combinations of employees of units. Expert knowledge and the Fishburne method were also used to determine the weights of the areas of knowledge. The map of knowledge of the enterprise, a hierarchical tree of areas of knowledge of the project with use of system of relations of advantages is constructed. A modified Harrington scale was used to assess the level of knowledge of potential project team members. The practical implementation of the model was carried out for a machine-building enterprise that plans to produce a new type of product. Out of 52 candidates, 23 were selected to form the project team. 4 of them require additional training from internal experts who are employees of the enterprise. The created model can be used by a wide range of enterprises taking into account the specifics of their activities.
Keywords: project team; optimization model; economic-mathematical model; enterprise knowledge management